Cost effective hydrogen production of coupled photovoltaic and electrolyzer systems considering plant lifetime and geographical location - D. Vizza; R. Caponi; E. Bocci; L. Del Zotto; C. Bassano (Energy Conversion and Management: X, 2025)
Advancements in electrolysis technologies, coupled with improvements in associated production processes and public incentive programs, are progressively enabling the widespread deployment of megawatt-scale electrolyzers. While these policies are crucial in the short term to support the adoption of emerging technologies and the transformation of industrial processes, substantial focus must be directed toward optimizing technical solutions. This study aims to determine the cost-optimal configuration of a grid-connected system comprising a photovoltaic (PV) production plant and an electrolyzer. This will be accomplished using advanced simulation models that account for the load and thermal cycles, the geographical location of production sites, and the operational lifespan of the installations. The simulation will identify the optimal ratio between the PV array and the electrolyzer to minimize the LCOH (Levelized Cost of Hydrogen). A sensitivity analysis of the PV capacity, considering site-specific irradiation, will be conducted to achieve this objective. The study further delves into the evaluation of the LCOH depending on the utilization of the stacks and alternative management control logic. The findings from the study suggest that the optimal PV:ELE ratio ranges from 1.5:1 to 1.8:1 based on geographical location and highlight an LCOH reduction of about 10 % while coupling the electrolyzer with a PV monoaxial tracking installation over a fixed setup. Ultimately, the analysis of alternative stack usage strategies demonstrates that dynamically balancing stack utilization ensures the lowest LCOH compared to all other tested alternatives.